“Human Papilloma Virus Vaccination for cervical cancer prevention. Is it safe and effective?” - Gunawardane, Damitha Asanga (Bangladesh Journal of Medical Science, 2018)
Human papillomavirus (HPV) causes cervical cancer, which is the fourth most common cancer in women. Most of the cervical cancers are linked to genital infection with HPV and it is the most common viral infection of the reproductive tract. At present, there are three types of HPV vaccines available. Even though HPV vaccination is a primary prevention tool, that does not eliminate the need for routine cervical screening, since the vaccines do not protect against all high-risk HPV types. Ninety percent of HPV infections have no clinical consequences at all whether they are high-risk or low-risk subtypes of HPV. All three types of HPV vaccines have very high vaccine efficacy for prevention of HPV infection among females aged 14 to 26 years. Proper assessment of the safety of HPV vaccine is a problem even after proper systematic review since the most of the clinical trials on the safety of the vaccines were used Hepatitis A vaccine or high immunogenicity enhancing aluminium adjuvant as their placebo. HPV vaccination would be very cost effective for the countries when there is no cervical screening program or if the programme coverage is very poor. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.329-336